Clinic-morphological aspects of the state of the fetoplacental complex at pregnant women with hyperandrogenism - S. V. Logvinov; L. A. Agarkova; O. G. Dish; N. A. Gabitova; O. A. Tikhonovskaya (Бюллетень сибирской медицины, 2006)
The study of the fetoplacental complex and the morphological research of placenta of 50 pregnant women with hyperandrogenism were conducted by the ultrasonic method, dopplerometry and cardiotocography. It was shown that hyperandrogenism causes destructive and neonatal adaptation changes of placenta leading to its dysfunction. The high frequently of occurrence of complications in the gestational process at late diagnostics of hyperandrogenism (during pregnancy) was observed.